KAVRA as a UX-based digital fashion learning platform: Integrating creative self-expression and brand identity communication - Sandra Alfiani; Dewi Istikhomah; Muhammad Fadhil Shidqi (Researcher and Lecturer Society, 2026)
This study examined the development and evaluation of KAVRA as a UX-based digital fashion learning platform that integrates creative self-expression and brand identity communication. The research addressed the limitations of existing fashion design tools, which often present high technical barriers and lack support for identity expression and communicative interaction. A design thinking methodology was employed, involving iterative stages of empathize, define, ideate, prototype, and test, with participants consisting of undergraduate fashion design students and industry practitioners. The findings showed that KAVRA achieved high usability performance across key dimensions, including navigation ease (88%), visual accessibility (85%), time efficiency (90%), information clarity (82%), intuitive design (82%), and overall user satisfaction (82%). These results indicated that the platform effectively supports digital fashion learning by reducing cognitive load and enabling efficient task completion. Beyond functional usability, the platform also facilitated user interaction and engagement through intuitive visual design and communicative interface structures. Importantly, the study demonstrated that UX functions as a strategic communication interface that enables users to express creative identity and construct personal brand meaning through digital fashion design activities. Features such as 3D visualization, design customization, and collaborative interaction support reflective design processes and social engagement. The study concludes that UX-based platforms can serve not only as instructional media but also as communicative environments that integrate learning, interaction, and identity construction. These findings provide theoretical and practical implications for the development of future digital learning systems in creative domains.